0638 Primary Hypothyroidism Is Associated With Individual Chronotypes In Adult Women. (12th April 2019) - Arosemena Coronel, Marilyn A; Ramos, Alberto; Marcus, Erin N; Castillo, Pablo R
Abstract: Introduction: Introduction: We aimed to determine whether thyroid hormone levels are associated to abnormal chronotypes in a clinical sample of females with hypothyroidism. We also hypothesized that abnormal chronotypes are frequent in hypothyroidism. Methods: A single center retrospective study conducted at an urban, south Florida ambulatory care clinic during years 2013-2015. Subjects included females with hypothyroidism due to autoimmune or acquired causes. Chronotype was based derived from The Munich ChronoType Questionnaire (MCTQ). The Mann-Whitney U test was used to compare demographic, sleep and thyroid stimulating hormone (TSH) level across chronotype groups (early vs. intermediate/late). Regression analysis was used to evaluate associations between chronotype and TSH levels adjusting for age, BMI, sleep duration and levothyroxine dose. Interaction terms were added to the fully adjusted models. Results: We evaluated a total of 99 patients with mean age of 56.5±7 years (range 22-65), BMI of 30.3±6.6 and sleep duration of 7.2±1.6. Fifty-eight percent had early onset chronotype, while 42% had intermediate or late chronotype. Multivariable analysis showed that BMI (F=10.46; p=0.002), early chronotype (F=10.6; p=0.002) and the interaction of BMI with chronotype (F=12.7; p=0.006) were associated with TSH adjusting for age, sleep duration and levothyroxine dose. Conclusion: Early chronotypes were more frequent in this sample of females with hypothyroidism. In particular, early chronotye with higher BMI was associated to increased TSH. Support (If Any): R21-AG056952 (ARR)